PEMBUATAN DAN KARAKTERISASI SUPPORT LAYER UNTUK MEMBRAN PERVAPORASI - Ariestya Meta Devi; Lulluil Mahsunnah; Heru Susanto (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro, 2012)
The selection of the membrane has an important role in the process of pervaporation membranes based on the advantages and disadvantages for use in the separation process.. In the separation process of water with low concentration and need a specific condition, anorganic membrane is suitable. The purpose of this research is to find the optimal composition of support for the preparation of zeolite membranes.The result of the research shown the support membrane with composition alumina : kaolin 56%wt : 34%wt has a highest strength 46,65 N/mm2 and 30,24 N/mm2 if it compare with composition of alumina : kaolin 45%wt : 45%wt and 34%wt : 56%wt. And then the support layer is depositioned by zeolite. As an identification result from XRD, it shown mullite as dominant phase that formed with crystal size range 3,16 – 7,25 nm. Based on the analysis results obtained using the SEM support surface which has been deposited into closer, but the zeolite crystals have not formed a bond that forms between each zeolite.